Influence of the centrifugation time in the soil-water retention curve in Cerrado soils - da Silva, Euzebio Medrado; de Azevedo, Juscelino Antonio (Pesquisa Agropecuaria Brasileira, 2002)
<!–[if gte mso 9]> Normal 0 <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> The centrifugation time, necessary to the equilibrium of soil moisture, is a determinant factor for the precision of the soil-water retention curve. The objective of this work was to evaluate the effect of the centrifugation time on the soil-water retention curve of five soil-types from the Cerrado region. The retention curves were adjusted using non-linear regression, with the sum of minimum square errors being used to evaluate the statistical differences among them. For each soil type, the obtained retention curves were presented as a family of curves to facilitate the visualization of differences among them. The results showed clearly that the time of centrifugation affects the retention curve, imposing a visible rotation on the curves, centered at the saturation point. Using the technique of the inverse regression, it was possible to calculate the necessary time of centrifugation for each soil type, based on the 5% significance level and 90% confidence interval. For the studied soils, the time of centrifugation necessary for extracting water from the soil sample up to equilibrium, at each applied rotation, using the traditional method of soil-centrifugation for determining soil-water retention curve, has to be over 80 minutes. <!–[if !supportLineBreakNewLine]–> <!–[endif]–>